Poseł burmistrzem, radny posłem: opinia publiczna wobec zjawiska przerywania kadencji - Kowalik, Janina (Political Preferences, 2017)
Deputy as a mayor, councilor as a deputy. The public opinion on the phenomenon of termination of mandate in elective bodies The main issue dealt with in this article pertains to a certain aspect of democratic rules, understood at large, occurring presently in Poland, which are: not serving full terms by various levels local government elected officials and members of parliaments (UE parliament included) due to running for other offices. Statistics of these practices are not reported by the State Board of Election, consequently estimating the level of this phenomenon is hard, for it requires following particular cases, which may lead to errors. While considering this author undertook an attempt to estimate this phenomenon. I will examine the issue of cutting short term due to candidacy for another position, from the legal point of view and then from the ethical and philosophical evaluation of such action with focus on the statistics of not fulfilling electoral term due to taking another preferred position. Finally I will examine how this affects public opinion according to Poland wide surveys conducted on representative samples at the turn of 2015 and 2016. Key words: local government, cadences, elections, party electoral politics